If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + 3) = 2(x + 3) + -3x Reorder the terms: 12(3 + x) = 2(x + 3) + -3x (3 * 12 + x * 12) = 2(x + 3) + -3x (36 + 12x) = 2(x + 3) + -3x Reorder the terms: 36 + 12x = 2(3 + x) + -3x 36 + 12x = (3 * 2 + x * 2) + -3x 36 + 12x = (6 + 2x) + -3x Combine like terms: 2x + -3x = -1x 36 + 12x = 6 + -1x Solving 36 + 12x = 6 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 36 + 12x + x = 6 + -1x + x Combine like terms: 12x + x = 13x 36 + 13x = 6 + -1x + x Combine like terms: -1x + x = 0 36 + 13x = 6 + 0 36 + 13x = 6 Add '-36' to each side of the equation. 36 + -36 + 13x = 6 + -36 Combine like terms: 36 + -36 = 0 0 + 13x = 6 + -36 13x = 6 + -36 Combine like terms: 6 + -36 = -30 13x = -30 Divide each side by '13'. x = -2.307692308 Simplifying x = -2.307692308
| 7h-14+17=3 | | 3(2x-3)-2x=-x+1 | | 3x+1*2x+1=22 | | 11s=15 | | 1.8/6.5=x/11 | | 81=15x(x-7) | | 5/6.5=x/11 | | 8x+72-11= | | 8-0.6x=23 | | 0.2x-3=9 | | 72d+45+13=12d-2 | | 6b^2-39b+63=0 | | 4(4-3)=3(2w+2) | | 2.4n=18 | | 7n^2+19n-36=0 | | 14.6m=284.7 | | 5*6=x | | -x+5x-22=-46 | | 11-3x=5x | | 11n-3=9+3n | | 4n-12+7n=20 | | 11*3=x | | 5xsquare=8x-6 | | x+(6/3)=20 | | 4/10n+1/10=5/10n+2 | | 2y-7y=5y-9y | | logx(21)=7 | | 9/14+10 | | 4x^2-12x-9=25 | | 9-(x-3)=20 | | -6x+30=-12 | | -3/4x=(-5/8) |